FIGURATIVE LANGUAGES IN BTS ALBUM LOVE YOURSELF: ANSWER - Luh Komang Mira Gradistina; Putu Desi Anggerina Hikmaharyanti (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2023)
This study aimed at analyzing BTS song lyrics and exploring more about the meanings of figurative languages. There were two theories used in this study, the first theory proposed by Kennedy (1983) for identifying the types of figurative languages and theory of meaning proposed by Leech (1974). This study applied qualitative method. Data were obtained from reading the lyric and listening to BTS songs, finding the word, phrase, and sentence containing figurative languages, taking notes on the types of figurative language, classifying the data into types of figurative language then analyzing the meaning. As a result, 5 types of figurative languages were found in BTS Album Love Yourself: Answer, they were Simile (20%), Metaphor (10%), Personification (5%), Hyperbole (50%), and Irony (15%). Hyperbole took the most dominant figurative language among other types. There were 5 out of 7 meanings found, affective meaning, stylistic or social meaning, thematic meaning, connotative meaning and reflective meaning.